Recessive Mutations in LEPREL1 Underlie a Recognizable Lens Subluxation Phenotype. (March 2015) - Khan, Arif O.; Aldahmesh, Mohammed A.; Alsharif, Hadeel; Alkuraya, Fowzan S.
Abstract Purpose: To uncover the homozygous recessive gene mutation underlying familial lens subluxation and/or juvenile lens opacities in four sisters from a consanguineous family. Methods: Prospective family study (clinical phenotyping; homozygosity-analysis-guided candidate gene testing). Results: The proband was a 14-year-old girl with long-standing poor vision, bilateral temporal lens subluxation, lens opacities, and axial high myopia. There were no syndromic findings, and fibrillin-1 sequencing was normal. Three sisters, also non-syndromic, had undergone bilateral juvenile lens surgery (two for juvenile cataract, 1 for lens subluxation) within the first two decades of life. Both sisters who had cataract surgery developed bilateral post-operative retinal detachments and one had documented lens instability during cataract surgery. Genetic analysis revealed the phenotype to segregate with a novel homozygous recessive mutation in LEPREL1 (c.292delC; p.Gly100Alafs*104). Recessive mutations in this gene were recently highlighted as a cause for axial myopia and early-onset cataract in two families for whom some affected members also had ectopia lentis and/or post-operative retinal detachments. Conclusions: Recessive LEPREL1 mutations should be recognized as part of the differential diagnosis of lens subluxation. The associated phenotype is non-syndromic and distinguishable from other causes of ectopia lentis in the context of its additional features: juvenile lens opacities, axial myopia, and a predisposition to retinal tears/detachment following intraocular surgery.